2006
DOI: 10.1051/0004-6361:20066264
|View full text |Cite
|
Sign up to set email alerts
|

The magnetic field of the pre-main sequence Herbig Ae star HD 190073

Abstract: Context. The general context of this paper is the study of magnetic fields in the pre-main sequence intermediate mass Herbig Ae/Be stars. Magnetic fields are likely to play an important role in pre-main sequence evolution at these masses, in particular in controlling the gains and losses of stellar angular momentum. Aims. The particular aim of this paper is to announce the detection of a structured magnetic field in the Herbig Ae star HD 190073, and to discuss various scenarii for the geometry of the star, its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
91
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 28 publications
13
91
0
Order By: Relevance
“…Our old measurements (Hubrig et al 2006a) revealed a magnetic field of the order of 80 G at the 2.8σ level, in full agreement with the high resolution ESPaDOnS spectropolarimetric data, whereas Wade et al (2007) failed to detect the magnetic field in both previous measurements carried out with FORS 1 in November 2004. Our new measurements B z = 104 ± 19 G using the full spectrum and B z = 120 ± 32 G using hydrogen lines confirm the results presented by Catala et al (2007). Baines et al (2006) reported the presence of a potential companion.…”
Section: Herbig Ae/be Stars With Detected Magnetic Fieldssupporting
confidence: 90%
See 1 more Smart Citation
“…Our old measurements (Hubrig et al 2006a) revealed a magnetic field of the order of 80 G at the 2.8σ level, in full agreement with the high resolution ESPaDOnS spectropolarimetric data, whereas Wade et al (2007) failed to detect the magnetic field in both previous measurements carried out with FORS 1 in November 2004. Our new measurements B z = 104 ± 19 G using the full spectrum and B z = 120 ± 32 G using hydrogen lines confirm the results presented by Catala et al (2007). Baines et al (2006) reported the presence of a potential companion.…”
Section: Herbig Ae/be Stars With Detected Magnetic Fieldssupporting
confidence: 90%
“…HD 190073: a magnetic field of B z = 74±10 G was detected using photospheric metal lines with ESPaDOnS (Catala et al 2007). Our old measurements (Hubrig et al 2006a) revealed a magnetic field of the order of 80 G at the 2.8σ level, in full agreement with the high resolution ESPaDOnS spectropolarimetric data, whereas Wade et al (2007) failed to detect the magnetic field in both previous measurements carried out with FORS 1 in November 2004.…”
Section: Herbig Ae/be Stars With Detected Magnetic Fieldsmentioning
confidence: 99%
“…Later on, this star was studied by Catala et al (2007) with ESPaDOnS observations, who confirmed the presence of a magnetic field, B z = 74 ± 10 G, at a higher significance level. A longitudinal magnetic field B z = 104 ± 19 G was reported by Hubrig et al (2009) using FORS 1 measurements.…”
Section: Hd 190073mentioning
confidence: 93%
“…The absorption and emission spectrum of the Herbig Ae star HD 190073 was studied in detail by Catala et al (2007) and more recently by Cowley & Hubrig (2012). The low projected rotational velocity (v sin i ≤ 9 km s −1 ) may indicate either a very slow rotation, or a very small inclination of the rotation axis with respect to the line of sight.…”
Section: Hd 190073mentioning
confidence: 99%
“…The intriguing spectrum of the magnetic Herbig Ae star HD 190073 (V1295 Aql) has attracted the attention of classical as well as modern spectroscopists (Merrill 1933;Swings & Struve 1940;Catala et al 2007, henceforth CAT). Pogodin, Franco & Lopes (2005, henceforth P05) give a detailed description of the spectrum along with a historical resume of investigations from the 1930's.…”
Section: Introductionmentioning
confidence: 99%